Maternal Outcome of Primigravida Patient with Term Pregnancy with Engaged Versus Unengaged Foetal Head at Onset of Labour - Samar Hussain, Saima Qurban, Huma Tahseen, Kiran Javed, Hafiza Naveeda Khurshid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the maternal outcome of primigravida patient with term pregnancy with engaged versus unengaged foetal head at onset of labour Design of the Study: It was a cohort study. Study Settings: The study was conducted at Department of Obstetrics & Gynecology Rashid Latif Medical College, Lahore from January 2021 to June 2021. Material and Methods: This study involved 160 primigravida at term (as per dating scan) aged between 18-35 years who were divided into cases (women with unengaged fetal head) and controls (those with engaged fetal head). Outcome variable were frequency of cesarean delivery, low birth weight, poor APGAR score at 1 and 5 minutes and NICU admission which were noted and compared between the groups. Results of the Study: The mean age of the patients was 23.9±3.8 years while the mean gestational age was 39.0±1.3 weeks. The frequency of poor APGAR score at 1 minute (25.0% vs. 5.0%; p-value<0.001; 95%CI RR=5.00) and cesarean delivery (38.8% vs. 16.3%; p-value=0.001; 95%CI RR=2.39) was significantly higher in women with unengaged fetal head at term. However, there was no statistically significant difference between the groups in terms of poor APGAR score at 5 minutes (5.0% vs. 2.5%; p-value=0.405; 95%CI RR=2.00), NICU admission (10.0% vs. 8.8%; p-value=0.786; 95%CI RR=1.14) and low birth weight (7.5% vs. 3.8%; p-value=0.303; 95%CI RR=2.00). Conclusion: In the present study, unengaged fetal head at term was associated with poor APGAR score at birth and increased risk of cesarean delivery which advocates that women with unengaged fetal head at term should be considered as high risk so that anticipated management may improve the fetomaternal outcome